PREVALENCE OF MASK USE DURING EXERCISE AT PUPUTAN MARGARANA RENON FIELD, DENPASAR CITY DURING THE COVID-19 PANDEMIC - Purnamsidi, Wilbert; Dinata, I Made Krisna; Adiatmika, I Putu Gede; Sugianto, Alena Juliani (E-Jurnal Medika Udayana; Vol 13 No 07 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i07.P01, 2024)
The Covid-19 pandemic requires people to wear masks as a preventive measure. In addition, exercise is also highly recommended because it can prevent metabolic and infectious diseases by boosting the immune system. During this period, the government issued several regulations regarding the obligation to wear masks which certainly affected people's sports activities, especially in public spaces such as Puputan Margarana Renon Field, Denpasar City. This study was conducted by means of visual observation to count the number of people who use masks and the types of masks used when exercising. The observations made obtained a total sample of 2023 people. A total of 737 people (36.43%) used masks while 1286 people (63.57%) did not use masks. This low prevalence of mask use can be based on several factors such as concern, discomfort, and non-compliance. The 737 mask users are divided into several types of masks used, including surgical masks (45.45%), KF94 masks (17.91%), duckbill masks (17.91%), cloth masks (8.01%), scuba masks (4.48%), and cloth mask with valves (0.81%). Each of these masks has its advantages assessed through the aspects of effectiveness, price, tightness, and various other aspects. Through this study, it can be concluded that the prevalence of using masks when exercising at Puputan Margarana Renon Field, Denpasar City is still quite low (36.43%) with the most commonly used masks being surgical masks (45.45%).